Effects of oxidative stress on the pharmacokinetics and hepatic metabolism of atazanavir in rats. (April 2013) - Kobuchi, S.; Fukushima, K.; Aoyama, H.; Ito, Y.; Sugioka, N.; Takada, K.
Abstract We studied the effects of oxidative stress (OS) on the pharmacokinetics of atazanavir (ATV), particularly the distribution of ATV in the plasma and its metabolism in hepatic microsomes, using a rat model of ferric-nitrilotriacetate-induced OS (OS rats). The areas under the plasma concentration–time curves for intravenous bolus, oral, and intraportal administration of ATV in the OS rats were significantly greater than those in the control rats, whereas blood clearance of ATV after intravenous bolus injection in the OS rats (0.94 ± 0.04 L/h/kg) was approximately half of that in the control rats (2.08 ± 0.20 L/h/kg). Moreover, the intrinsic clearance (CLint), which is determined by in vitro metabolic studies using hepatic microsomal fractions of rats, was approximately 43% lower in the OS rats (0.489 ± 0.017 mL/min/mg protein) than in the control rats (0.851 ± 0.004 mL/min/mg protein). ATV concentrations in both the plasma-bound fraction and erythrocytes of the OS rats were significantly greater than those in the control rats. These results suggest that the hepatic metabolism of ATV may be reduced in patients under OS.